Inflammatory cues enhance TGFβ activation by distinct subsets of human intestinal dendritic cells via integrin αvβ8 - Fenton, T; Kelly, A; Shuttleworth, E; Smedley, C; Atakilit, A; Powrie, F; Campbell, S; Nishimura, S; Sheppard, D; Levison, S; Worthington, J; Lehtinen, M; et al. (Springer Nature, 2016)
Regulation of intestinal T-cell responses is crucial for immune homeostasis and prevention of inflammatory bowel disease (IBD). A vital cytokine in regulating intestinal T cells is transforming growth factor-β (TGFβ), which is secreted by cells as a latent complex that requires activation to function. However, how TGFβ activation is regulated in the human intestine, and how such pathways are altered in IBD is completely unknown. Here we show that a key activator of TGFβ, integrin αvβ8, is highly expressed on human intestinal dendritic cells (DCs), specifically on the CD1c(+) but not the CD141(+) intestinal DC subset. Expression was significantly upregulated on intestinal DC from IBD patients, indicating that inflammatory signals may upregulate expression of this key TGFβ-activating molecule. Indeed, we found that the Toll-like receptor 4 ligand lipopolysaccharide upregulates integrin αvβ8 expression and TGFβ activation by human DC. We also show that DC expression of integrin αvβ8 enhanced induction of FOXP3 in CD4(+) T cells, suggesting functional importance of integrin αvβ8 expression by human DC. These results show that microbial signals enhance the TGFβ-activating ability of human DC via regulation of integrin αvβ8 expression, and that intestinal inflammation may drive this pathway in patients with IBD.